2015
DOI: 10.1249/jsr.0000000000000160
|View full text |Cite
|
Sign up to set email alerts
|

Medical Planning for Very Large Events

Abstract: Mass gathering events that involve special populations have challenges that require unique medical planning. The key to a successful mass event is in the preparation, planning, and communication. Concerns in communication such as language barriers, age of participants, and intellectual disability should be addressed early in the planning. In the event of a mass casualty disaster, there should be a clear chain of command and escalation policy. The primary concern of the sports medicine team is to ensure safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The key factor for success is the combination of preparation, planning, and communication. Previously, several trials for the preparation and planning of mass gathering sports events have been reported [ 11 13 ]. The present study focused on spectator medicine in the stadium, not for the athlete and general travellers.…”
Section: Discussionmentioning
confidence: 99%
“…The key factor for success is the combination of preparation, planning, and communication. Previously, several trials for the preparation and planning of mass gathering sports events have been reported [ 11 13 ]. The present study focused on spectator medicine in the stadium, not for the athlete and general travellers.…”
Section: Discussionmentioning
confidence: 99%
“…6 Finally, a report of medical planning for a large SO event (World Games Los Angeles 2015) had focused on logistical considerations within US events but did not analyze injury data in athletes. 7 Given these limited data on SO injuries from previous studies, it is important to study the full breadth of injuries at a large SO event.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges add to the usual logistical planning for venues and events used for any large-scale competition. 7 Given the frequency and scale with which SO events are held worldwide, we aimed to analyze the injury trends in SO athletes to inform medical teams of injury trends in preparation for future events.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] There should be medical rescue teams who are particularly trained for particular injuries expected to happen according to the type of sports events. [ 21 ] Medical rescue teams should be physically, psychologically, and technically ready in a perfect way. [ 21 ] In Formula 1 Singapore Night Races, PPR was found to be 2.7, and Transport to Hospital Rate was 0.034.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Medical rescue teams should be physically, psychologically, and technically ready in a perfect way. [ 21 ] In Formula 1 Singapore Night Races, PPR was found to be 2.7, and Transport to Hospital Rate was 0.034. [ 22 ] The majority of applications/admissions (%58.7) in races are musculoskeletal injuries which include fluid retention, lacerations, abrasions, sprains, and strains.…”
Section: Introductionmentioning
confidence: 99%